IDENTIFICATION OF ARCHITECTURAL ELEMENTS IN THE OLD TEUNGKU MOSQUE IN PUCOK KRUENG DISTRICT. PIDIE JAYA - Sulwana Suci; Cut Azmah Fithri; Hendra Aiyub (RADJA PUBLIKA, 2026)
The Tengku Old Mosque in Pucok Kreung is a historic building with significant architectural, cultural, and religious value for the community. As a building that has undergone development and change over time, the existence of architectural elements in this mosque needs to be identified and documented to maintain its character and authenticity. This study aims to identify the characteristics of architectural elements in the Tengku Old Mosque in Pucok Kreung through theory (Ching, 2007; Naibaho & Pakpahan, 2024). The elements analyzed include floors, walls, columns or supporting structures, doors, windows, ventilation, ceilings, and roofs. This study uses a descriptive qualitative method with a case study approach. Data collection was carried out through field observations, documentation, and interviews with parties knowledgeable about the history and development of the mosque. Data analysis was carried out by identifying the physical condition, function, visual or aesthetic, and symbolic value contained in each architectural element. The results show that the Tengku Old Mosque in Pucok Kreung still retains most of the characteristics of traditional architectural elements that reflect the architectural identity of ancient mosques in Aceh. Each element has a structural and spatial function that supports worship activities, while also containing aesthetic and symbolic values ​​that enhance the building's character. Although some elements have undergone changes due to renovations and functional needs, the mosque's primary character as a historic building is still recognizable through its form, materials, and architectural arrangement. This research is expected to serve as a reference in efforts to preserve and develop historic mosque buildings while still maintaining their architectural values.